Intramedullary nailing through a suprapatellar approach. Evaluation of clinical outcome after removal of the device using the infrapatellar approach - Noia, Giovanni; Fulchignoni, Camillo; Marinangeli, Maurizio; Maccauro, Giulio; Tamburelli, Francesco Ciro; De Santis, Vincenzo; Vitiello, Raffaele; Ziranu, Antonio (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Since 2006, It has been developed the possibility to introduce a tibia nail through a suprapatellar access. However, the removal of device must be carried out using the classic infrapatellar approach. The aim of this study is to evaluate the clinical scores of a group of patients that removed a tibial nail by infrapatellar approach, previously introduced through a suprapatellar access. Methods: Seven patients received removal, through infrapatellar access, of tibial nail previously introduced by suprapatellar approach. Despite being VAS